Somatic Distance, Cultural Affinities, Trust and Trade - Jacques Melitz; Farid Toubal (Center for Economic Studies and ifo Institute (CESifo), 2018)
Somatic distance, or differences in physical appearance, proves to be extremely important in the gravity model of bilateral trade in conformity with results in other areas of economics and outside of it in the social sciences. This is also true quite independently of survey evidence about bilateral trust. These findings are obtained in a sample of the 15 members of the European Economic Association in 1996. Robustness tests also show that somatic distance has a more reliable influence on bilateral trade than the other cultural variables. The article finally discusses the interpretation and the breadth of application of these results.
Keywords: F10; F40; Z10; 330; somatic distance; cultural interactions; trust; language; bilateral trade